The anti-Islamism discourse; the case of al-Buti - Bakour Mohamad, Bachar; Berghout, Abdul Aziz (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
This paper explores al-Būṭī’s critical view on contemporary Islamists who, according to al-Būṭī, have misapplied the Islamic law and sacrificed da‘wah in favour of political gains. Among their dogmatic beliefs is the ruthless and hasty call for the establishment of the Islamic state, the takfīr of rulers, arbitrary application of the question of tatarrus, etc. Having presented and evaluated al-Būṭī’s views pertaining to Islamists’ position on the above issues, the paper further attempts to examine whether they are applicable to contemporary movements or not. This was done through consulting the literature of the most eminent Islamist movements (Ḥizb al-Taḥrīr, the Muslim Brotherhood, jihadists, the AKP, and Ḥizb al-Nahḍa). The paper followed textual analysis aspiring towards providing a more comprehensive approach to the study of al-Būṭī’s views. Accordingly, seven important issues were selected and used to assess the position of movements according to al-Būṭī’s approach. It concludes, that al- Būṭī’s anti-Islamist discourse deserves to be taken as a yardstick against which a clear distinction is made between extreme and moderate Islamist movements. The paper also suggested several measures to further enhance research in this important area of study.